Tax smoothing with immigration in an overlapping generations economy - Lopez-Velasco, Armando R. (Applied economics letters, 2019)
Immigration policy in an overlapping generations economy is politically determined in response to government spending shocks, where the government finances its spending with proportional income taxes and is subject to a balanced budget. The young cohort is always the majority and dictates policy. The equilibrium Markovian strategy allows immigrants when the spending shock is above some threshold and this implies a particular form of tax smoothing.